Financial Performance and Dividend Policy for Economic Resilience : Evidence from LQ45 IDX - Livia Naomi; Ratna Juwita (MDP Student Conference, 2026)
This study aims to analyze the effect of profitability and company growth on dividend policy among companies included in the LQ45 Index listed on the Indonesia Stock Exchange during the period 2019–2024. The scope of this research focuses on firms with high liquidity and large market capitalization, representing leading companies in the Indonesian capital market. This study employs a quantitative method using secondary data obtained from annual financial statements, with sample selection conducted through purposive sampling, resulting in 120 observations. Multiple linear regression analysis is applied using SPSS Statistics 26 to test the proposed relationships. The results indicate that Return on Assets (ROA) and company growth have a significant effect on dividend policy, both partially and simultaneously. These findings suggest that data-based financial indicators can serve as a basis for investment decision-making and dividend policy formulation, contributing to corporate stability and capital market resilience amid evolving economic dynamics.